Long-Term Survival of Cutaneous Malignant Melanoma with Metastasis to Paranasal Sinuses: A Case Report and Literature Revie - Javadinia, Seyed Alireza (Galen Medical Journal, 2018)
Background: Malignant melanoma (MM) usually present with metastases to unexpected regions of the body. Metastatic MM is a highly lethal condition, and the median survival in this setting is 6 to 7.5 months; however, few reports rarely describe long-term after chemotherapy.Case Report: We describe a 31-year-old man with MM, which got metastatic (to paranasal sinuses) after local and systemic therapy showed complete responses with long-term survival after endonasal endoscopic metastasectomy and radiotherapy of the nasal cavity, paranasal sinuses, and base of the skull.Conclusion: Although long-term survival is rare, few reports describe cases after chemotherapy. MM could be associated with metastasis to any regions and clinicians should be aware of its behavior and perform complete investigation in the presence of any suspicious symptoms, and this should be reinforced periodically. However, the survival is poor in the metastatic setting, and the treatment of choice is debatable, some patients may benefit from metastasectomy and local radiotherapy. [GMJ.2018;7:e860]